Clinico-Haemato-Biochemical Alterations and Therapeutic Management of Bovine Theileriosis - Prajapati, Krishna D.; Raval, Sunant K.; Mandali, Ghanashyam C.; Rao, Neha; Bhavsar, Shailesh K.; Bharai, Munja (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Theileriosis is an economically important haemoprotozoan disease of cattle caused by Theileria spp. It causes production losses and mortality in dairy industry. A total of 135 cattle suspected of theileriosis were screened based on clinical signs and blood smear examination (Giemsa’s stain). Out of them, 64 animals were diagnosed with theileriosis. Twenty-four cattle out of them were selected and divided into four equal groups, viz., B, C, D, and E, each comprised of six animals for four different treatment protocols to evaluate their therapeutic efficacy, while group A of six healthy cattle served as control. The most common clinical findings of theileriosis infected cattle (n = 24) in descending order were anorexia (100%), dullness and depression, decreased milk production, weakness, salivation, enlarged pre-scapular lymph nodes, pale conjunctival mucous membrane, presence of ticks over the body, emaciation, nasal discharge, cessation of rumination, lacrimation, diarrhea and sternal recumbency (8.33%). The mean rectal temperature, heart rate, and respiratory rate were 104.5 ± 0.33° F, 79.5 ± 2.85/min and 42.83 ± 2.67/min, respectively. The haematological findings revealed decreased values of haemoglobin, packed cell volume, total erythrocytes count (TEC), lymphocytes, and mean corpuscular hemoglobin concentration (MCHC), and increased values of neutrophils, eosinophils, Mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH) in theileriosis infected cattle as compared to healthy cattle. Biochemical findings revealed decreased values of total protein and albumin while increased total bilirubin, Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), and Gamma-glutamyl transferase (GGT) in theileriosis-infected cattle. These altered haemato-biochemical profiles were found to be normalized by the 14th day in different treatment groups. The therapeutic efficacy of Buparvaquone 2 dose (Group B) and Buparvaquone plus Oxytetracycline LA (Group D) was better (100.00%) than the Arteether (Group C, 66.66%) and Arteether plus Oxytetracycline LA (Group E, 83.33%) in theileriosis infected cattle, hence may be advocated to the field veterinarians for effective treatment of theileriosis in cattle.